(untitled) (Al-Aasar, 2025)
In the contemporary financial system, the application of Artificial Intelligence (AI) and Machine Learning (ML) has not only enhanced the efficiency of business operations but has also introduced new dimensions in investment, risk management, data protection, and automated financial decision-making. However, when this technology enters the domain of Islamic banking, it raises significant jurisprudential and ethical questions. Since Islamic banking is fundamentally grounded in the principles of Shariah and moral values, the central inquiry is whether AI-driven decisions can remain aligned with the standards of justice, transparency, trustworthiness, and the boundaries of halal and haram. Within this framework, the present study seeks to contextualize classical jurisprudential principles particularly those related to riba, gharar, and maysir in relation to the practical applications of AI. Ethical considerations such as the boundaries of human agency versus machine decision-making, algorithmic bias, consumer rights, data privacy, and integrity have also been critically examined in the light of Islamic ethics. Furthermore, the research incorporates insights from classical jurists, contemporary fiqh institutions such as the International Islamic Fiqh Academy (IIFA) and AAOIFI, as well as modern Islamic scholars and technology experts, to present a comprehensive outlook. The findings suggest that the use of AI and ML in Islamic banking is not only possible but can also be highly beneficial, provided its application remains faithful to the higher objectives of Shariah (Maqāṣid al-Sharīʿah), namely justice, transparency, human welfare, and financial stability. For this purpose, the study underscores the necessity of ijtihād, regulatory supervision, and the formulation of an ethical framework, ensuring that modern technology serves the cause of human welfare while preserving the supremacy of Shariah.